Dynamic phasor modelling of multi-generator variable frequency electrical power systems - Yang, Tao; Bozhko, Serhiy; Le-Peuvedic, Jean-Mark; Asher, Greg; Hill, Christopher Ian (IEEE, 2016)
The Dynamic Phasor (DP) concept has been widely used in modelling electrical power systems. So far, the DP concept has been restricted to modelling systems with one single electrical source at a fixed fundamental frequency; either one generator or an ideal three-phase AC source. This paper aims to extend the DP modelling methodology to a wider application area. Two major achievements have been introduced: 1. application of DPs for multi-source, multi-frequency systems; 2. modelling of systems with time-varying frequencies. These two techniques enable the use of DPs to study nearly all types of Electrical Power Systems (EPS). The developed theory is validated using a twin-generator system from the More Open Electrical Technologies (MOET) project. The accuracy and effectiveness of the developed models is confirmed by comparing the simulation results of detailed switching models and DP models under both balanced and unbalanced conditions.